Determining Participant’s Satisfaction in Mining Safety Training Using Service Quality Model and Importance-Performance Analysis - Supardi Supardi; Jumawan Jumawan; Andrian Andrian (Universitas Sang Bumi Ruwa Jurai, 2022)
Feedback from participants showed that 15.9% of them were not satisfied with the given training services. The purpose of this study was to find out participants’ satisfaction with the training service provided by the mining safety training providers. In this study, the applied data analysis techniques were the service quality (ServQual) model and importance-performance analysis (IPA) by comparing the perceptions and expectations desired. The total of respondents was 167 people who were participants of training organized by Inspirasi Safety from September to November 2020. The results of the ServQual analysis showed that, in the dimensions of reliability and responsiveness, they indicated a negative gap and the service rate of below 100%, meaning that, in these dimensions, the participants were not satisfied with the provided services. Meanwhile, for the dimensions of tangible, assurance, and empathy, the results indicated that participants were satisfied. In addition, the results of the importance-performance analysis indicated that the service criteria that need to be improved were the timeliness of starting and finishing the training and the fast response to participants’ complaints. Furthermore, this study is expected to be able a suggestion for training providers to pay more attention to the service quality given to participants.